(untitled) (Research, Society and Development, 2023)
The pandemic caused by the COVID-19 virus has had implications for the health of pregnant women and the premature birth of their babies. In order to investigate the experience of this population, this paper aims to produce an Integrative Review. The results and discussions presented here are part of a larger study that is still under development. To this end, the searches were systematized and carried out in the CAPES Periodicals database, with the descriptions: ’prematurity’, ’covid-19’, ’pregnancy’, ’neonatal ICU’. The inclusion criteria were articles available in full, in Portuguese and English, published from 2020 onwards, with free access and that had an affinity with the theme. Initially, 3 articles were included, dealing with possible complications in pregnancy due to the disease, a literature review on current knowledge of COVID-19 in the gestational period and the experiences of mothers of infants who were born prematurely during the pandemic. The results show impacts caused by the pandemic on the experience of prematurity, with points of distinction and similarity with what is experienced outside this scenario, as well as revealing a gap in knowledge regarding qualitative research on the subjective experience of this population with premature birth in the condition of contamination by the virus.